LIPUS Promotes Calcium Oscillation and Enhances Calcium Dependent Autophagy of Chondrocytes to Alleviate Osteoarthritis - Mengtong Guan; Xiaoyu Han; Bo Liao; Wang Han; Lin Chen; Bin Zhang; Xiuqin Peng; Yu Tian; Gongyi Xiao; Xinhe Li; Liang Kuang; Ying Zhu; et al. (Advanced Science)
Abstract Osteoarthritis (OA) is a degenerative disease which places an enormous burden on society, effective treatments are still limited. As a non‐invasive and safe physical therapy, low‐intensity pulsed ultrasound (LIPUS) can alleviate OA progression, but the underlying mechanism is not fully understood, especially the mechanical transduction between LIPUS and the organism. In this pioneering study, the biomechanical effects of LIPUS on living mice chondrocytes and living body zebrafish are investigate by using fluorescence imaging technology, to dynamically “visualize” its invisible mechanical stimuli in the form of calcium oscillations. It is also confirmed that LIPUS maintains cartilage homeostasis by promoting chondrocyte autophagy in a calcium‐dependent manner. In addition, chondrocyte ion channels are screened by scRNA‐seq and confirm that the mechanosensitive ion channel transient receptor potential vanilloid 4 (TRPV4) mediated the biological effects of LIPUS on chondrocytes. Finally, it is found that a combination of pharmacologically induced and LIPUS‐induced Ca2+ influx in chondrocytes enhances the cartilage‐protective effect of LIPUS, which may provide new insights for optimizing LIPUS in the treatment of OA.